Frame drums in the world: a documentation proposal (Per Musi, 2023)
There is a wide variety of frame drums in the music and culture of different traditions around the world. With similar structural characteristics, they are organized into the same “family” of instruments, differing by morphological variants, forms of execution, timbre and contexts of use. This article lists and documents a series of frame drums from bibliographical sources, showing their histories, their organological characteristics, forms of execution and aspects of their musicality. This work is part of a research developed around the subject “pandeiro”, which highlights the relevance of percussion in dialogue with areas of historical and documentary research in music.